Bulk density of forested mineral soils. - Tamminen, Pekka; Starr, Michael (The Finnish Society of Forest Science and The Finnish Forest Research Institute, 2009)
Relationships between bulk density and organic matter (OM) content, textural properties and depth are described for forested mineral soils from central and northern Finland. Core samples were taken of the 0–5, 30–35 and 60–65 cm layers at 75 plots. Three measures of bulk density were calculated: the bulk density of the < 20 mm fraction (BD20), the bulk density of the < 2 mm fraction (BD2), and laboratory bulk density (BDl). BDl was determined from the mass of a fixed volume of < 2 mm soil taken in the laboratory. All three measures of bulk density were strongly correlated with organic matter content (r ≥ –0.63). Depth and gravel (2–20 mm) content (in the case of BD2) were also important variables. BDl was sensitive to clay contents > 7% but did significantly improve the prediction of both BD2 and BD20 in coarse soils (clay contents ≤ 7%). The following predictive models were derived for coarse soils: BD2 = 0.7668 – 0.08523 · – 0.01217 · Gravel + 0.1852 · Depth + 0.4318 · BDl, R2 = 0.86 and BD20 = 0.4718 – 0.01598 · OM + 0.3125 · Depth2 + 0.5962 · BDl, R2 = 0.86 (BD2, BD20 and BDl in kg/dm3, OM content as % of < 2 mm oven-dry soil and Gravel content as % < 20 mm air-dry soil, and Depth in m).